Velocity effects on Piezocone measurements in normally and over consolidated clays. Issue 2 (June 2007) - Schneider, James A.; Lehane, Barry M.; Schnaid, Fernando
Abstract : Cone penetration tests (CPTs) performed under controlled conditions in a centrifuge can improve understanding and interpretation of CPT data obtained in the field. However, the cone diameter and cone penetration velocity employed in the centrifuge differ significantly from their respective full scale values and the effect of these scale differences need to be understood to allow extrapolation to the field. This paper examines the influence of cone velocity on tip resistance and penetration pore pressures, and also investigates trends during pore pressure dissipation when cone penetration is halted. Piezocone penetration tests were performed at different rates in normally consolidated and overconsolidated specimens of clay and silty clay in a beam centrifuge. The penetration rate was varied by over four orders of magnitude to provide information on partially drained and undrained penetration resistance and on the associated pore pressure response. The overconsolidation ratio and silt content are shown to have significant effect on the rate dependency of cone tip resistance and pore pressures.